Neutrino and gravitational wave signal of a delayed-detonation model of type Ia supernovae - Seitenzahl, Ivo R.; Herzog, Matthias; Ruiter, Ashley J.; Marquardt, Kai; Ohlmann, Sebastian T.; Röpke, Friedrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The progenitor system(s) and the explosion mechanism(s) of type Ia supernovae (SNe Ia) are still under debate. Nonelectromagnetic observables, in particular, gravitational waves and neutrino emission, of thermoclear supernovae are a complementary window to light curves and spectra for studying these enigmatic objects. A leading model for SNe Ia is the thermonuclear incineration of a near-Chandrasekhar mass carbon-oxygen white dwarf star in a “delayed detonation.” We calculate a three-dimensional hydrodynamic explosion for the N100 delayed-detonation model extensively discussed in the literature, taking the dynamical effects of neutrino emission from all important contributing source terms into account. Although neutrinos carry away 2×1049 erg of energy, we confirm the common view that neutrino energy losses are dynamically not very important, resulting in only a modest reduction of final kinetic energy by 2%. We then calculate the gravitational wave signal from the time evolution of the quadrupole moment. Our model radiates 7×1039 erg in gravitational waves and the spectrum has a pronounced peak around 0.4 Hz. Depending on viewing angle and polarization, we find that the future space-based gravitational wave missions DECIGO and BBO would be able to detect our source to a distance of ∼1.3 Mpc. We predict a clear signature of the deflagration-to-detonation transition in the neutrino and the gravitational wave signals. If observed, such a feature would be a strong indicator of the realization of delayed detonations in near-Chandrasekhar mass white dwarfs.
Gesehen am 16.06.2020